Similar bleeding phenotype in young children with haemophilia A or B: a cohort study. (3rd June 2014) - Clausen, N.; Petrini, P.; Claeyssens‐Donadel, S.; Gouw, S. C.; Liesner, R.; PedNet; Research of Determinants of Inhibitor development (RODIN) Study Group
Summary The bleeding phenotype has been suggested to differ between haemophilia A and B. More knowledge on the bleeding phenotype at initiation of treatment is important to optimize patient care. The aim of this study was to investigate the severity of the bleeding phenotype and the variation in bleeding in children with severe or moderate haemophilia A and B. Consecutive, previously untreated patients with severe or moderate haemophilia A and B (factor VIII or IX activity <0.01 or 0.01–0.05 IU mL−1 respectively) born between January 1st 2000 and January 1st 2010 were included. Primary outcome was severity of bleeding tendency. Secondary outcome was variation in bleeding pattern. A total of 582 patients with severe haemophilia A and 76 with severe haemophilia B did not differ in age at first exposure to clotting factor (0.81 vs. 0.88 years, P = 0.20), age at first bleed (0.82 vs. 0.88 years, P = 0.36), and age at first joint bleed (1.18 vs. 1.20 years, P = 0.59). Patients with moderate haemophilia were older compared to patients with severe haemophilia. In patients with moderate haemophilia there were no clear differences between haemophilia A and B. Severity and variation in bleeding phenotype are similar during the early stage of treatment in patients with severe and moderate haemophilia A and B respectively. The findings imply that children with haemophilia B should be observed and treated as vigilantly as those with haemophilia A.